The budget program in the context of public management - Nunes, André; Oliveira, Ricardo Borges; Beú, Rivany Borges (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The article analyzes the ability of the budget program be effectively used as a tool at the service of an efficientand or effectivepublic management, considering the present institutional limitations in PublicAdministration in Brazil. Thereforeit seeks to understand whether thebudgetprogramis integrated into government planning –Pluriannual Plan,Budget Guidelines Lawand to Annual Budget Law-or if itisjust an accounting and financial instrumentinstead a management tool. To facilitate the analysis, aimed to investigatethrough a literature review, the practice of public management, the budget public and the relationamongthem in the context of public andbudgetary management in Brazil.